The incidence of infection in routine knee arthroscopy without the use of prophylactic antibiotics is low. (June 2019) - Lai, Mun Chun; Yeo, William; Tan, Andrew Hwee Chye
Background: The use of prophylactic antibiotics in routine knee arthroscopy remains prevalent despite previous evidence suggesting that it may not be necessary, and may indeed carry more risks than benefits. This study aims to determine the incidence of surgical site infections in patients undergoing routine knee arthroscopy without prophylactic antibiotics. Methods: This is a retrospective review of 553 consecutive patients who underwent routine knee arthroscopy from 2004 to 2013 by a single fellowship-trained sports surgeon in a single institution. The spectrum of cases included arthroscopic meniscectomy, meniscal repair, microfracture, chondroplasty, removal of loose bodies and lateral retinacular release. No patient received any prophylactic antibiotics. Patient demographics and comorbidities were reviewed and all patients were followed up postoperatively for a minimum of two years. All postoperative complications were recorded. Results: There were 349 male and 204 female patients. The mean age was 41.8 years (SD 14.8) and mean operative time was 30.4 minutes (SD 12.3). Two healthy young patients developed postoperative superficial wound infection within one week after surgery, but recovered with outpatient oral antibiotic treatment. The overall infection rate was 0.36%. No cases of deep infection were reported. Conclusion: This study showed a very low rate of surgical site infections, comparable with known rates following such operations. This suggests that prophylactic antibiotics are not necessary and avoids the known risks associated with their use.